Molecular and phenotypic characterization of the sensitivity of Corynespora cassiicola to site- specific fungicides - Sacon, Deivid (2020)
Target spot caused by Corynespora cassiicola is an important leaf disease, capable of causing economic losses in several crops, including soybean and cotton. For the management of this disease, chemical control is major component, but site-specific fungicide resistance has become a major concern. Sequences of target gene of MBC (Methyl Benzimidazoles Carbamates), QoI (Quinone Outside Inhibitors), DMI (Demethylation Inhibitors) and SDHI (Succinate Dehydrogenase Inhibitors) fungicides in 79 C. cassiicola isolates obtained from soybean and cotton samples collected from Brazilian producing regions during 2017-2020 were characterized, and the impact of nucleotide changes leading to amino acid substitutions in the sensitivity to these fungicides was addressed by quantifying in vitro mycelial growth inhibition. Nucleotide polymorphism leading to E198A and F200Y substitutions in β-tubulin, G143A in CytB, B-H278Y and C- N75S / A in the SDH were found. G143A that usually leads to high level of resistance in fungi to QoIs was present in 87% of the isolates surveyed; F129L and G137R substitutions were not detected. The E198A substitution in β-tubulin provided greater resistance to carbendazim compared to F200Y. B-H278Y, C-N75S /A substitutions conferred cross resistance to the fungicides benzovindiflupir, fluxapyroxade and inpyrfluxam and provided similar resistance levels; however, a stronger effect on fluxapyroxad sensibility was verified. No variation in the DMI target site (Cyp51) nor resistance to the prothioconazole DMI was observed. Substitutions leading to multiple resistance to fungicides MBC, QoI, and SDHIs fungicides was identified in 20 isolates. Target site mutations leading to amino acid substitution in C. cassiicola specically associated with isolates from cotton or soybean were not detected. These results provide an overview of the current situation of fungicide resistance of C. cassiicola from cotton and soybean providing information for better chemical management of target spot in these crops. Keywords: DMI. MBC. QoI. SDHI. Target spot.